2021
DOI: 10.3389/fenrg.2021.722514
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Comparative Performance Evaluation of a Hybrid Photovoltaic-Thermoelectric System

Abstract: The majority of incident solar irradiance causes thermalization in photovoltaic (PV) cells, attenuating their efficiency. In order to use solar energy on a large scale and reduce carbon emissions, their efficiency must be enhanced. Effective thermal management can be utilized to generate additional electrical power while simultaneously improving photovoltaic efficiency. In this work, an experimental model of a hybrid photovoltaic-thermoelectric generation (PV-TEG) system is developed. Ten bismuth telluride-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 44 publications
2
8
0
1
Order By: Relevance
“…Also, only one thermoelectric module was used, and the concentrated solar irradiance was not very high (less than 20 Suns). Nevertheless, Khan et al [18] reported that when ten thermoelectric modules were used under higher solar fluxes, the performance enhancement provided by the thermoelectric became more apparent. In all cases, the thermoelectric generator still contributed to the performance enhancement of the photovoltaic system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, only one thermoelectric module was used, and the concentrated solar irradiance was not very high (less than 20 Suns). Nevertheless, Khan et al [18] reported that when ten thermoelectric modules were used under higher solar fluxes, the performance enhancement provided by the thermoelectric became more apparent. In all cases, the thermoelectric generator still contributed to the performance enhancement of the photovoltaic system.…”
Section: Resultsmentioning
confidence: 99%
“…Although the feasibility of the photovoltaic-thermoelectric system has been demonstrated using various theoretical and experimental methods [18,19], there is still room for further enhancements in system efficiency [20][21][22]. The system's performance can be further increased by optimizing the geometry of the thermoelectric generator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another commonly used method is to place TE modules directly underneath PV panels, with PV panels acting as the hot sides of TE modules. Khan et al [ 12 ] performed an experimental study of such configurations, and the results showed that the T PV could be decreased by 3 K, and consequently, the total output power was increased by 19% and the overall solar‐to‐electric efficiency was increased by 17% with respect to the bare PV panels. The TE modules that operated alone under solar irradiation conditions were also studied.…”
Section: Introductionmentioning
confidence: 99%
“…Among these proposed techniques, the thermoelectric cooling method stands out due to the relative effectiveness, commercial availability, and affordability of the thermoelectric module (TEM) in cooling the concentrated solar photovoltaic (CPV) system [13][14][15]. Some researchers have experimentally demonstrated how the CPV-TE hybrid system was capable of generating a higher power and efficiency than the stand-alone CPV system by utilizing the entire broad solar spectrum [16][17][18][19]. Khan et al [16] recorded a 5.5% drop in the solar cell temperature and a subsequent 17% increase in the overall system's efficiency when TEMs were integrated with PVs.…”
Section: Introductionmentioning
confidence: 99%